192_pdfsam_math 54 differential equation solutions odd

192_pdfsam_math 54 differential equation solutions odd -...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Chapter 4 (b) The auxiliary equation to the differential equation obtained in (a) is 3r 2 + 8r − 3 = 0, which has the roots r= −8 ± 64 − 4(3)(−3) −8 ± 10 = 6 6 ⇒ r = −3, 1 . 3 This yields a general solution y (t) = c1 et/3 + c2 e−3t . (c) Since x = et , we can express y (t) as a function of x by writing y = c1 et/3 + c2 e−3t = c1 et 1/3 + c2 et −3 = c1 x1/3 + c2 x−3 . 41. This equation is a Cauchy-Euler equation. The substitution x = et leads to the equation (22) with a = 1, b = 2, and c = −6. Thus we have a dy d2 y + (b − a) + cy = 0 2 dt dt ⇒ d2 y dy + − 6y = 0. dt2 dt The auxiliary equation, r 2 + r − 6 = 0, has the roots r = −3 and r = 2. Therefore, a general solution can be written as y = c1 e−3t + c2 e2t = c1 et 43. The substitution x = et yields the equation dy d2 y + (9 − 1) + 17y = 0 dt2 dt ⇒ dy d2 y + 8 + 17y = 0. dt2 dt −3 + c2 et 2 = c1 x−3 + c2 x2 . Solving the characteristic equation, r 2 + 8r + 17 = 0, we get √ −8 ± 64 − 68 = −4 ± i. r= 2 Thus, the roots are complex with α = −4, β = 1, and a general solution, as a function of t, is given by y (t) = c1 e−4t cos t + c2 e−4t sin t. Now we make the back substitution. Since x = et , we have t = ln x and so y = et 188 −4 (c1 cos t + c2 sin t) = x−4 [c1 cos(ln x) + c2 sin(ln x)] . ...
View Full Document

Ask a homework question - tutors are online